Strategi Inovatif Odd One Out dalam Materi Pronunciation di Sekolah Dasar - Heru Prasetyo; Novita Sari (CV. Jalan Cendikia, 2025)
This Community Service (PKM) activity is motivated by the limited variety of English pronunciation learning strategies in elementary schools, which has an impact on low student involvement, lack of sound differentiation practice, and lack of confidence when practicing pronunciation. This PKM aims to improve teachers' competence in designing and implementing innovative